STUDY ON THE MANAGEMENT OF LEARNING MEDIA IN SUPPORTING TEACHING AND LEARNING ACTIVITIES AT SMP NEGERI 13 SAMARINDA - Setya, Setya; Warman, Warman (Unmul Civic Education Journal, 2021)
The purpose of this study is to find out how to plan, procure and maintain learning media in supporting teaching and learning activities at SMPN 13 Samarinda. This type of research is descriptive and qualitative. Data sources are primary data and secondary data. This research focused on the management of learning media. The time for the implementation of the research was from October to December 2017. Data collection techniques consist of observation, interviews, and documentation while data analysis consists of data reduction, data presentation, and conclusion. The results showed that the planning for the procurement of learning media at SMPN 13 Samarinda had been carried out through the stage of identifying school needs. In the implementation of the procurement of learning media, it is carried out jointly by the school from the purchase and manufacture of learning media held by schools, teachers, and students, with procurement steps empowering all existing resources and considering the situation and supporting conditions for learning. Maintenance is carried out regularly both after use and inattention.